Long-Term Observations of Thickness Changes of Each Retinal Layer following Macular Hole Surgery - Atsushi Tada; Shigeki Machida; Yuji Hara; Satoshi Ebihara; Masahiko Ishizuka; Mana Gonmori (Journal of Ophthalmology)
Purpose. To determine the long-term changes of the thickness of each retinal layer following macular hole (MH) surgery combined with internal limiting membrane (ILM) peeling. Method. The medical records of 42 eyes of 42 patients (41 to 86 years of age) who underwent MH surgery with ILM peeling between February 2016 and October 2018 were reviewed. A single surgeon operated on all patients, and all were followed for at least 24 months postoperatively. Spectral-domain optical coherence tomography (OCT) was performed to obtain retinal thickness maps of the parafoveal region corresponding approximately to the ILM peeled area. Each retinal layer was automatically segmented by the embedded software, and thickness maps were constructed for the total retinal layer (TRL), inner RL (IRL), middle RL (MRL), and outer RL (ORL). The averaged value of each retinal layer thickness was analyzed in the temporal/upper, temporal/lower, nasal/upper, and nasal lower quadrants. Results. The TRL thickness was significantly decreased in the temporal areas postoperatively. The IRL thickness thinned progressively and significantly until 6 months without further thinning in the temporal quadrants. The MRL thickness of all areas was significantly thicker than the baseline values at 0.5 months and then gradually decreased in the temporal regions. However, the thickening in the nasal regions returned to the baseline values after 1.5 months. The ORL decreased transiently relative to the baseline values at 0.5 months in all areas. Conclusions. The ILM peeling does not affect only the thickness of the inner retina but also the middle and outer retinae in the parafoveal region. The chronological changes of the thickness after surgeries varied among the retinal layers and macular regions.